The problems of formalized social control of illegal wildlife trade in Poland = Die Probleme der formalisierten sozialen Kontrolle des illegalen Wildtierhandels in Polen - Drzazga, Edyta (Kriminologie - das Online-Journal, 2024)
This article considers the problem of counteracting illegal trade in wild fauna and flora in Poland, with a particular focus on exploring formalized social control of CITES crimes. Social controls to rein in sup-ply and demand for wild fauna and flora face certain inherent drawbacks. To effectively counteract illegal trade in wild fauna and flora, it is necessary to recognize the patterns of the phenomenon and to design a social and criminal policy that will provide an adequate response to both the supply of the phenomenon and its demand. The main aim of the project was therefore to present the results of qualitative research conducted with experts dealing with the phenomenon of illegal trade in wild fauna and flora in Poland.